Integrated Postsecondary Education Data System (IPEDS): Institutional Characteristics, 1987-1988 ([Verlag nicht ermittelbar], 1999)
This collection offers data on basic characteristics of postsecondary institutions in the United States and covers institutional characteristics for 1987-1988. The data were used for sample design and selection for other IPEDS surveys. Key data elements include the name, address, and telephone number of the institution, as well as information about levels of course offerings, calendar system, admissions requirements, student services, accreditation, modes of instruction, and institutional eligibility for student financial aid programs. Updated information on tuition, fees, and room and board charges for the current academic year also is available. The unit of analysis is the postsecondary institution.